2004
DOI: 10.1063/1.1774276
|View full text |Cite
|
Sign up to set email alerts
|

Cavity enhancement of the magneto-optic Kerr effect for optical studies of magnetic nanostructures

Abstract: We present a study of cavity enhancement of the magneto-optic Kerr effect using dielectric multilayers in order to facilitate optical studies of individual single-domain nanomagnets. We develop a transfer matrix theory to analyze Kerr rotation from an arbitrary number of possibly lossy dielectric layers. The combination of one lossless and one thin metallic layer is found to be most favorable for studying individual nanomagnets, providing the best tradeoff between signal enhancement and spatial resolution. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 18 publications
2
42
0
Order By: Relevance
“…The photonic effect can also be used to enhance the MOKE because of multiple interference of light within the magnetic multilayers [34][35][36] . Cavity enhancement of the MOKE has also been reported, in which a dielectric layer acts as a Fabry-Perot optical cavity [37][38][39] . Metamaterials, i.e., composite nanostructured materials, can also show enhancement of the MOKE [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…The photonic effect can also be used to enhance the MOKE because of multiple interference of light within the magnetic multilayers [34][35][36] . Cavity enhancement of the MOKE has also been reported, in which a dielectric layer acts as a Fabry-Perot optical cavity [37][38][39] . Metamaterials, i.e., composite nanostructured materials, can also show enhancement of the MOKE [40][41][42] .…”
Section: Introductionmentioning
confidence: 99%
“…No additional dielectric layers have been added to enhance the Kerr signal. 6 The membranes are not necessary for the MOKE measurements but allow for additional time resolved scanning transmission X-ray microscopy experiments on the same sample.…”
mentioning
confidence: 99%
“…MO enhancement up to a factor of 4 has been obtained using a single dielectric lm, 7) and has reached a value of approximately 16 (θ K ~ 1.6 ) by using a SiO 2 dielectric lm with a thin gold-coating layer. 9) In our system, the CoPt layer acts as a dual functional layer, ful lling the roles of both magnetic and coating lms. As discussed in Section B, we obtained an extraordinary enhancement factor of approximately 200 (θ K ~ 20 ) for a CoPt/AZO/Ag stacked lm.…”
Section: Effect Of a Zno Intermediate Layer On Copt/agmentioning
confidence: 99%
“…Similarly, MO cavities consisting of stacked layer structure enhance the MO effect by multiple re ections of light inside the structure. [6][7][8][9][10] The cavities are typically formed by a re ective layer as a mirror, magnetic layer, a spacer and a capping layer. In recent years, it has been reported that the MO cavities indicate a relatively large Kerr rotation angle reaching to several degrees.…”
Section: Introductionmentioning
confidence: 99%